Maturational patterns of left ventricular rotational mechanics in pre-term infants through 1 year of age. (15th September 2020) - Lehmann, Gloria C.; Levy, Philip T.; Patel, Meghna D.; Sekarski, Timothy; Gu, HongJie; Choudhry, Swati; Hamvas, Aaron; Singh, Gautam K.
Abstract: Background: Pre-mature birth impacts left ventricular development, predisposing this population to long-term cardiovascular risk. The aims of this study were to investigate maturational changes in rotational properties from the neonatal period through 1 year of age and to discern the impact of cardiopulmonary complications of pre-maturity on these measures. Methods: Pre-term infants (<29 weeks at birth, n = 117) were prospectively enrolled and followed to 1-year corrected age. Left ventricular basal and apical rotation, twist, and torsion were measured by two-dimensional speckle-tracking echocardiography and analysed at 32 and 36 weeks post-menstrual age and 1-year corrected age. A mixed random effects model with repeated measures analysis was used to compare rotational mechanics over time. Torsion was compared in infants with and without complications of cardiopulmonary diseases of pre-maturity, specifically bronchopulmonary dysplasia, pulmonary hypertension, and patent ductus arteriosus. Results: Torsion decreased from 32 weeks post-menstrual age to 1-year corrected age in all pre-term infants (p < 0.001). The decline from 32 to 36 weeks post-menstrual age was more pronounced in infants with cardiopulmonary complications, but was similar to healthy pre-term infants from 36 weeks post-menstrual age to 1-year corrected age. The decline was due to directional and magnitude changes in apical rotation over time (p < 0.05). Conclusion: This study tracks maturational patterns of rotational mechanics in pre-term infants and reveals torsion declines from the neonatal period through 1 year. Cardiopulmonary diseases of pre-maturity may negatively impact rotational mechanics during the neonatal period, but the myocardium recovers by 1-year corrected age.